Modifikasi Balok Beton Komposit Tulangan Bambu Profil Dari Lilitan Kawat Bendrat Guna Meningkatkan Daktilitas Dan Efisiensi Biaya Untuk Konstruksi Bangunan Gedung - (Jurusan Teknik Sipil Politeknik Negeri Semarang), Marsudi, Martono, Nursetiaji Pamungkas, Suroso, D (Teknis, 2015)
Iron concrete is a product of mine whose existence will someday run out. To overcome these probem, as an alternative to the use of molten tried bamboo cheap and high-power, In this study, bamboo is used as a substitute for reinforcement in concrete beams is simple. All the beams were cast bamboo beam bendrat wire windings. In the end it will be known how much Ability beam modification with reinforcement of bamboo which is entwined with wire petung bendrat in resisting bending style. From the test results strong urge concrete cubes can be deduced that the average compressive strength of concrete is 232 kg / cm2 means that the average quality of the concrete is to have K-232, higher than the plan that is the quality of K-225). Results of testing the tensile strength of concrete steel ï 6 mm obtained an average value of 15 kN, whereas for the reinforcement of babu petung ridden with iron bendrat obtained average value of 12 kN. The test results of concrete beam flexural strength of bamboo modification with reinforcement wire windings obtained an average of 17 kN test results, testing was stopped after concrete blocks have cracks, which addressed the collapse attractiveness of bamboo reinforcement wire coil bendrat. While the testing of concrete beams of concrete steel reinforcement ï 6 mm discontinued after the compressive strength reaches an average of 46 kN, because in this condition the beams have crack.Keywords: concrete beams, reinforcing bamboo, flexural strength.